Imaging of scleroma in the head and neck - Abdel Razek, A A K (The British Institute of Radiology., 2012)
We review the appearance of scleroma in the head and neck on imaging. Scleroma is a chronic granulomatous disease that primarily affects the nasal cavity, but the pharynx and larynx may also be involved. On imaging, nasal scleroma appears as bilateral or unilateral expanded homogeneous nasal masses that may exhibit hyperintense signal on T(1) weighted images. Pharyngeal scleroma commonly narrows the pharyngeal lumen and may involve the soft and hard palate. Imaging is essential to detect the extent of subglottic stenosis in patients with laryngeal scleroma. Rarely, scleroma may involve the orbit or the middle ear. Imaging is essential for the early diagnosis of scleroma and for differentiating it from other granulomatous and neoplastic lesions. Also, imaging is important for treatment planning and follow-up of patients after therapy.